Pemberian Larutan Gula Garam dan Istirahat Pendek dalam Menurunkan Beban Kerja Pekerja Bagian Produksi Perusahaan Roti â€Xâ€ Kota Semarang - Widjasena, Baju (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACK Background : Hot climate can increase body temperature, and then increase skin blood flow, heart beat rate, blood pressure, sweat rate and decrease gastrointestinal function. High sweat rate causes water-electrolyte imbalance in the body. Because of water-electrolyte imbalance, the body felt to dehidration. In dehydration, the work pulse will arise and make the work load arised. At “X’ Bakery, The climate over the threshold level, so the worker suffer dehydration. In order to cope the problems, the study about water-electrolyte consumption and short pauses was done. The aim of this study was to know the effects of carbohydrate-electrolyte consumption and short pauses to work load. Mehtods : The design of the study was Within-subject design with 16 subjects (8 man & 8 women) .There was two treatment in this study. Work load was determined by measure the work pulse with ten pulses method. The data was analyzed with T-paired Test (a = 0.05). Results : The result showed that carbohydrate-electrolyte intake and short pauses can significantly decrease work pulse 42,13% (p<0,05) . Conclusion : Based on the result, it is concluded that water-electrolyte intake and short pauses can significantly decrease the work load . It is suggested that worker and management has to improve the intervention Keywords : carbohydrate-electrolyte solution intake, short pauses, hot climate, worker